Argentinian multicenter study on urinary tract infections due to Streptococcus agalactiae in adult patients - Vigliarolo, Laura (2019)
Introduction Streptococcus agalactiae (group B streptococcus, GBS) is a recognized urinary pathogen both in males and pregnant or non-pregnant women. Data regarding GBS serotypes recovered from urinary tract infections (UTIs) are scarce. The aim of this study was to describe the clinical and microbiological characteristics of UTIs caused by GBS in adult patients in Argentina. Methodology A prospective multicenter study involving 86 centers was conducted in Argentina between July 1st, 2014 and June 30th, 2015. Antimicrobial susceptibility and serotype distribution of GBS isolated from the urinary tract of adult patients were determined. Susceptibility tests were performed by the disk diffusion and/or agar dilution methods. Epidemiological and clinical characteristics of the patients were considered to identify associated comorbilities. Results Seven hundred and one GBS were sent to the reference laboratory in the above mentioned period, however, only 211 fulfilled our selection criteria (demographic data availability, underlying diseases reported, colony counts greater than 105 CFU/mL, single organism isolated from the urine sample). No penicillin-resistant GBS was found but fluoroquinolone resistance was high (12.8%), especially among GBS isolated from men and non-pregnant women. UTIs due to GBS were associated to underlying diseases in men and non-pregnant women, particularly diabetes mellitus. Most of the isolates showed serotypes Ia and III. Conclusions GBS are still susceptible to penicillin but fluoroquinolone resistance is a growing concern, at least in Argentina. There are underlying conditions that could be associated to urinary infections caused by GBS.